2010
DOI: 10.1577/t08-174.1
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Swimming Behavior of Lake Trout Observed Using Integrated Multibeam Acoustics and Biotelemetry

Abstract: Multibeam echo sounder systems allow the in situ observation of swimming and foraging behavior and give insights into the ecology of fish at the individual level. In Lake Opeongo, Ontario, 16 adult lake trout Salvelinus namaycush were surgically implanted with ultrasonic tags, released, and studied by means of mobile fisheries acoustics. The transmitted pulses from the ultrasonic tags could be detected and displayed within the multibeam echogram in real time. Tagged lake trout were relocated on 131 occasions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The apparent confirmation of the “constant satiation hypothesis” in our study is contingent on the assumption that our daytime observations of activity are dominated by foraging behaviours. Several lines of evidence support this assumption: (a) lake trout are the apex predator in our study systems and hence should not exhibit predator avoidance behaviours; (b) our observations were temporally well separated from the known spawning season and hence should not be confounded with reproductive behaviours; (c) our observations were focused on the final foraging period prior to spawning, when energy acquisition through foraging is a primary determinant of future reproductive success; hence, foraging should be a priority activity; (d) the shift in activity patterns from night to day is consistent with that expected when a visual predator resumes foraging in daylight (i.e., in all lakes, the proportion of resting state detections was higher at night and the median activity level was lower); (e) lake‐to‐lake differences in water temperatures selected by lake trout varied in concert with temperature preferences of primary prey: colder temperatures were selected in lakes (Lakes 373 and Opeongo) with pelagic cold‐water prey, while warmer temperatures were selected in lakes with warm‐water epilimnetic/littoral prey (e.g., Lake Louisa); and (f) in the active dataset, the distribution of daytime values for a typical individual is skewed left with a heavy right‐hand tail; this is consistent with the feeding behaviour typical of a predatory feeder like lake trout where foraging activity is dominated by “low”‐intensity prey search behaviours, interrupted by short‐term bursts of high intensity associated with attempts at prey capture; (e.g., Dunlop, Milne, Ridway, Condiotty, & Higginbottom, —a study of lake trout predation on cisco in Lake Opeongo).…”
Section: Discussionsupporting
confidence: 60%
“…The apparent confirmation of the “constant satiation hypothesis” in our study is contingent on the assumption that our daytime observations of activity are dominated by foraging behaviours. Several lines of evidence support this assumption: (a) lake trout are the apex predator in our study systems and hence should not exhibit predator avoidance behaviours; (b) our observations were temporally well separated from the known spawning season and hence should not be confounded with reproductive behaviours; (c) our observations were focused on the final foraging period prior to spawning, when energy acquisition through foraging is a primary determinant of future reproductive success; hence, foraging should be a priority activity; (d) the shift in activity patterns from night to day is consistent with that expected when a visual predator resumes foraging in daylight (i.e., in all lakes, the proportion of resting state detections was higher at night and the median activity level was lower); (e) lake‐to‐lake differences in water temperatures selected by lake trout varied in concert with temperature preferences of primary prey: colder temperatures were selected in lakes (Lakes 373 and Opeongo) with pelagic cold‐water prey, while warmer temperatures were selected in lakes with warm‐water epilimnetic/littoral prey (e.g., Lake Louisa); and (f) in the active dataset, the distribution of daytime values for a typical individual is skewed left with a heavy right‐hand tail; this is consistent with the feeding behaviour typical of a predatory feeder like lake trout where foraging activity is dominated by “low”‐intensity prey search behaviours, interrupted by short‐term bursts of high intensity associated with attempts at prey capture; (e.g., Dunlop, Milne, Ridway, Condiotty, & Higginbottom, —a study of lake trout predation on cisco in Lake Opeongo).…”
Section: Discussionsupporting
confidence: 60%
“…This is surprising and contrary to their proximity with the lake bottom. Previous studies have demonstrated lake trout spend the majority of their time within close proximity to the lake bottom and coordinate prey encounters by attacking pelagic prey from below (Dunlop et al, ). Substrate characteristics appear to be irrelevant given this feeding mode.…”
Section: Discussionmentioning
confidence: 99%
“…Biotelemetry is one method to infer selection within a habitat envelope. This is achievable in smaller lakes (Plumb & Blanchfield, 2009) but technically challenging in large lakes (Dunlop et al, 2010;Morbey et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…several hours) collected using ad hoc sampling protocols (e.g. a mobile transducer along the channel to track the school or the methodology used by Dunlop et al (2010), which combines ultrasonic tagging with multibeam acoustic observations). However, the maximum observation time recorded during our study (34 s) did not allow us to apply such analysis.…”
Section: Discussionmentioning
confidence: 99%